From historical breakthroughs to a modern framework for antibiotic discovery - Ananya Anurag Anand; Sarfraz Anwar; Vidushi Yadav; Ayush Amod; Asim Nath; Sintu Kumar Samanta (Biologia, 2026)

Non canonical perspectives on AmpR mediated ampC expression in Gram negative bacteria, with particular emphasis on the potential regulatory purview of FtsZ - Sachin Kumar Gupta; Ananya Anurag Anand; Sarfraz Anwar; Sreyanki Chandra; Ayush Amod; Sintu Kumar Samanta (World Journal of Microbiology and Biotechnology, 2026)

Exploring the potential health risks of groundwater arsenic and its spatial distribution in three districts (Patna, Bhojpur and Saran) of Bihar, India - Parimal Kumar Khan; Pankaj Kumar; Anupma Kumari; Deepak Kumar Jha; Farha Ashique; Amod Kumar (Environmental Geochemistry and Health, 2026)

Advanced flexible composite films of Ti₃C₂Tₓ MXene-CCTO-PVDF for high-performance TENG-based self-powered sensor applications - Amar Dev; Amod Kumar; Tupan Das; Pawan Kumar; S.K. Pradhan; P. Kour; Manoranjan Kar (Chemical Engineering Journal, 2026)

Genetic estimates of growth traits in a small Yak population using Bayesian approach - Aneet Kour; Martina Pukhrambam; Amod Kumar; Varinder Singh Raina; Vijay Paul; Dinamani Medhi; Mihir Sarkar (Tropical Animal Health and Production, 2026)

Impact of a Community-based Intervention Program on Nutritional Status of Children Aged Under 5 Years With Undernutrition in Western Rural Nepal - Rajan Paudel; Yogendra Bahadur Gurung; Bijay Khatri; Amod Kumar Poudyal; Dilaram Acharya; Dipak Prasad Upadhyaya; Jitendra Kumar Singh; Mohan Paudel; Ramswarth Sah; Kwan Lee; Min Raj Adhikari; Ranjan Sapkota; et al. (Journal of Nutrition Education and Behavior, 2025)

Diagnostic and therapeutic strategies in combating implanted medical device-associated bacterial biofilm infections - Ayush Amod; Ananya Anurag Anand; Amaresh Kumar Sahoo; Sintu Kumar Samanta (Folia Microbiologica, 2025)

Genomic insights into high-altitude adaptation and evolutionary dynamics of Indian yaks in the Trans-Himalayan region - Karan Mahar; Ankita Gurao; Amod Kumar; Meenakshi Chitkara; Gopal Ramdasji Gowane; Sonika Ahlawat; Saket Kumar Niranjan; Rakesh Kumar Pundir; Reena Arora; Ranjit Singh Kataria; Mahesh Shivanand Dige (Conservation Genetics, 2025)

Advancing equine genomics: the development of a high density Axiom_Ashwa SNP chip for Indian horses and ponies - Sonika Ahlawat; Saket Kumar Niranjan; Reena Arora; Ramesh Kumar Vijh; Amod Kumar; Upasna Sharma; Meenal Raheja; Kanika Popli; Seema Yadav; Sharat Chandra Mehta (Functional & Integrative Genomics, 2024)

A Specialized and Comprehensive Resource of Antiviral Peptides against Ebola Virus - Rajat Kumar Mondal; Ananya Anurag Anand; Ayush Amod; Debayan Karmakar; Oshin Pal; Sintu Kumar Samanta (International Journal of Peptide Research and Therapeutics, 2024)

Monitoring and regression analysis of landfill surface temperatures using remote sensing and image processing techniques - Kislaye Sharma; Meenakshi Sood; Amod Kumar (International Journal of Remote Sensing, 2024)

Techno‐economic feasibility of year‐round use of drip irrigation in a rice‐ based cropping system* - Pravukalyan Panigrahi; Rabindra Kumar Panda; Sachin Kanta Rautaray; Sachidulal Raychaudhury; Amod Kumar Thakur; Atmaram Mishra (Irrigation and Drainage, 2021)
The water use, yield and profitability in three cropping sequences (rice–capsicum–baby corn, rice–rice–baby corn and rice–rice) grown under a drip irrigation (DRI) layout were compared with that in a rice–rice system under surface irrigation (SI) in a rice‐dominated region of eastern India. The DRI could save 37% of irrigation water without affecting the yield in rice compared with SI. The DRI in the rice–capsicum–baby corn cropping system produced 4.63 times higher yield (rice equivalent yield, 48.2 t ha‾¹) using 59% less water (7570 m 3 ha‾¹), resulting in 11 times higher water productivity (8.72 kg rice m‾ 3 water), 7.63 times higher annual net income (NI) (435 000 INR ha‾¹) and 18 times higher economic water productivity (EWP) (INR 78.7 m‾ 3 water) with a benefit–cost ratio (BCR) of 2.87 compared with the rice–rice cropping system under SI. Use of DRI in a multi‐cropping sequence is recommended for higher water productivity and net profit in rice‐based cropping systems in irrigated commands.

Immune responses and immunoprotection in crustaceans with special reference to shrimp - Amod Kulkarni; Sreedharan Krishnan; Deepika Anand; Shyam Kokkattunivarthil Uthaman; Subhendu Kumar Otta; Indrani Karunasagar; Rajendran Kooloth Valappil (Reviews in Aquaculture, 2021)
Crustacean aquaculture, dominated by shrimp, is a highly profitable food‐producing sector in the world. However, a variety of biotic and abiotic stressors can have adverse effect on the immune system of shrimp making them susceptible to diseases. Although a vertebrate‐like adaptive immune system is lacking in shrimp, an efficient innate immune system renders protection against invading pathogens. The innate immune system comprises two distinct but overlapping components, the cellular and humoral, and these are regulated through several signal transduction pathways. The signal pathways are initiated by the recognition of pathogen‐associated molecular patterns by germline‐encoded pattern recognition receptors leading to the production of different effector molecules that act against the pathogens. RNAi‐mediated post‐transcriptional gene silencing and microRNA regulation of immune response have also been found to be functional in shrimp. Similarly, apoptosis and apoptosis‐related genes are also reported, besides interferon (IFN) system‐like antiviral regulatory mechanism. Further, some form of immune memory, termed ‘immune priming’ or ‘innate immunity with specificity’ and ‘quasi‐immune response’ is recorded in shrimp and these abilities have been exploited in verifying the immunoprotection against different pathogens. Antigens developed either directly from the pathogens or through recombinant proteins have been tested for immune‐protective ability. RNAi‐mediated protection has also been demonstrated against different shrimp viruses. This review summarizes the available scientific information on immune responses and the immunoprotection trials carried out in crustaceans with a focus on shrimp. The available research evidences indicate the potential of developing effective immunoprophylactic measures in shrimp.

Risk assessment of low arsenic exposure using biomarkers of oxidative and genotoxic stress in a piscine model - Deepak K. Jha; Kumar Sayrav; Gaurav P. Mishra; Bipin B. Mishra; Anupma Kumari; Amod Kumar; Parimal K. Khan (Ecotoxicology, 2019)

The mRNA expression of immune-related genes in crossbred and Tharparkar cattle in response to in vitro infection with Theileria annulata - Prashant Dewangan; Manjit Panigrahi; Amod Kumar; B. C. Saravanan; Shrikant Ghosh; V. N. Muhashin Asaf; Subhashree Parida; G. K. Gaur; Deepak Sharma; Bharat Bhushan (Molecular Biology Reports, 2015)

In-silico search of virus-specific host microRNAs regulating avian influenza virus NS1 expression - V. N. Muhasin Asaf; Amod Kumar; Ashwin Ashok Raut; Sandeep Bhatia; Anamika Mishra (Theory in Biosciences, 2015)

Assessment of Arsenic-Induced DNA Damage in Goldfish by a Polymerase Chain Reaction-Based Technique Using Random Amplified Polymorphic DNA Markers - Amod Kumar; Vibudh P. Kesari; Ashok Kumar Alok; Syed N. Kazim; Parimal K. Khan (Archives of Environmental Contamination and Toxicology, 2014)

Impact of water management on yield and water productivity with system of rice intensification (SRI) and conventional transplanting system in rice - Amod Kumar Thakur; Rajeeb Kumar Mohanty; Dhiraj U. Patil; Ashwani Kumar (Paddy and Water Environment, 2014)

Does toll-like receptor-3 (TLR-3) have any role in Indian AMD phenotype? - Neel Kamal Sharma; Kaushal Sharma; Amod Gupta; Sudesh Prabhakar; Ramandeep Singh; Pawan Kumar Gupta; Akshay Anand (Molecular and Cellular Biochemistry, 2014)

Induction of sperm impairments in mice as a sensitive biomarker of arsenic toxicity - Vibudh P. Kesari; Amod Kumar; Parimal K. Khan (Environmental Monitoring and Assessment, 2014)

Initiatives for earthquake disaster risk management in the Kathmandu Valley - Amod Mani Dixit; Ryuichi Yatabe; Ranjan Kumar Dahal; Netra Prakash Bhandary (Natural Hazards, 2013)

Differential responses of system of rice intensification (SRI) and conventional flooded-rice management methods to applications of nitrogen fertilizer - Amod Kumar Thakur; Sreelata Rath; Krishna Gopal Mandal (Plant and Soil, 2013)

Fish micronucleus assay to assess genotoxic potential of arsenic at its guideline exposure in aquatic environment - Amod Kumar; Vibudh P. Kesari; Parimal K. Khan (BioMetals, 2013)

Effects on rice plant morphology and physiology of water and associated management practices of the system of rice intensification and their implications for crop performance - Amod K. Thakur; Sreelata Rath; D. U. Patil; Ashwani Kumar (Paddy and Water Environment, 2011)